2018
DOI: 10.1038/s41598-018-35976-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Specific Ultrastructure of Capillary Endothelial Glycocalyx and Its Possible Contribution for Blood Brain Barrier

Abstract: Endothelial glycocalyx coats healthy vascular endothelium and plays an important role in vascular homeostasis. Although cerebral capillaries are categorized as continuous, as are those in the heart and lung, they likely have specific features related to their function in the blood brain barrier. To test that idea, brains, hearts and lungs from C57BL6 mice were processed with lanthanum-containing alkaline fixative, which preserves the structure of glycocalyx, and examined using scanning and transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(182 citation statements)
references
References 40 publications
4
177
0
1
Order By: Relevance
“…We recently reported that the structures of the endothelial glycocalyx differ greatly among the brain, heart, and lung. 23 In this report, the pulmonary capillary glycocalyx is constructed of a thin layer; therefore, it is particularly difficult to detect its structure without ultrastructural imaging. Likewise, in a quantitative assessment of protein expression by Western blot analysis, it is impossible to confirm that the endothelial glycocalyx actually exists on the inner surface of the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the structures of the endothelial glycocalyx differ greatly among the brain, heart, and lung. 23 In this report, the pulmonary capillary glycocalyx is constructed of a thin layer; therefore, it is particularly difficult to detect its structure without ultrastructural imaging. Likewise, in a quantitative assessment of protein expression by Western blot analysis, it is impossible to confirm that the endothelial glycocalyx actually exists on the inner surface of the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The luminal surface of the capillary endothelium is covered by the EC glycocalyx (Ausprunk et al, 1981a, b; Pillinger and Kam, 2017). Brain ECs have a denser glycocalyx than peripheral vasculature; average glycocalyx coverage is 40.1% in brain vessels compared with 15.1% and 3.2% in cardiac and pulmonary vessels, respectively (Ando et al, 2018). This dense network of luminal glycoproteins prevents larger molecules from interacting with the EC.…”
Section: The Nvumentioning
confidence: 99%
“…9). Recently, the brain's NVU ecGCx has been beautifully studied, visualized and documented by lanthanum nitrate staining by both transmission electron microcopy (TEM) and scanning electron microscopy (SEM) making this EC surface coating layer visible even though TEM preparations undergo numerous dehydration steps [67]. The perfusion fixation with lanthanum nitrate presacrifice allows the ecGCx to be beautifully stained and visualized with TEM and SEM studies from cortical brain regions of the C57B6 mice ( Fig.…”
Section: Endothelial Glycocalyx (Ecgcx)mentioning
confidence: 99%